Introduction to Adobe Experience Design (XD) : learn the basics of using Adobe XD to prototype web sites and apps without having to code anything (O'Reilly, 2017)
"Adobe XD lets designers be designers by making it possible for them to create working prototypes of web sites and apps without writing a single piece of code. Adobe expert Andy Anderson teaches the basics of using Adobe XD and the process of building prototypes in this hands-on course where you don't just see the software, you use it to design an actual working prototype of a very tasty cooking app."--Resource description page.